Climate change effect on the cooling performance and assessment of passive daytime photonic radiative cooler in India - Bijarniya J.P.; Sarkar J. (My University, 2025)
In the long future, dependency on conventional air conditioning systems for thermal comfort certainly needs to be reduced, with alternate strategies like passive photonic radiative cooling. Recent metamaterial development with highly reflective in the solar spectrum pushes the radiative cooling technique toward application assessment. In this paper, the photonic radiative cooler performance is analyzed for year 2019 at various Indian locations considering the diversity of climate and forecasted for year 2030. The effect of three types of climate change is considered: geographical, seasonal and year-wise. Some photonic coolers with different emissive profiles are also compared. As the radiative cooling depends upon air temperature, humidity, wind speed and solar flux intensity, the effects of influencing climatic or weather parameters during summer months are studied extensively and major performance influencing factors are identified. Photonic radiative cooler performance in energy-saving as rooftop envelope assisted to conventional air conditioning system is assessed and observed cooling energy saving of 25–32 kWhth/month for selected locations. Study reveals that the windshield is the necessary condition to get net cooling flux through the rooftop. The reduction of cooling load on active systems of 34% is observed for low humidity locations with the integration of radiative cooler as a roof envelope. © 2020 Elsevier Ltd